PERENCANAAN LONG STORAGE PADA BENDUNG CIPERO KABUPATEN TEGAL - Andy Yogananda Imawan; Mohamad Agus Faozan; Suharyanto Suharyanto; Priyo Nugroho (Jurnal Karya Teknik Sipil, 2015)
Cipero weir is located at Tegal, The weir was built in 1888 and functioned to fulfill Rambut irrigation area water needs. The condition of Cipero weir is not able to fulfill all of Rambut irrigation area water needs. This condition is caused by several things. It is because of the reduction of Cipero catchment area in the upstream, more over the sedimentation in the upstream of Cipero make the weir is not functioning optimally. the solution is necessary to build Cipero long storage, Long storage Cipero is an elongated building, located at Cipero River that will increasing the availability of water for Rambut irrigation area. The analysis in the planning of Cipero Long Storage consists of three main parts. The first is hydrological analysis, then Hydraulics calculation phase and design phase of the building. Hydrological analysis phase aims to determine the flood discharge, the discharge mainstay, and the water needs in Rambut irrigation area. The second phase is the phase of hydraulics calculation, This phase aims to determine the dimensions of long storage building. , The third stage is the phase of design, This is a calculation of the cost of Cipero long storage. In this study is showed that the long storage can fulfill the water needs in the amount of 40.835.047,680 m3 every year. it can be concluded that the Cipero long storage can increase the amount of available water for irrigation area Rambut.